Caracterização fenotípica e molecular da susceptibilidade antimicrobiana em Serratia marcescens isoladas de pacientes em um hospital terciário do estado de Tocantis - Rezende, Graziela Silva (Universidade Federal de São Carlos, 2019)
Serratia marcescens is a member of Enterobacteriaceae familly with intrinsic resistance to various antimicrobial groups. In this study, 54 strains of Serratia marcescens isolated from patients admitted to the intensive care unit of a tertiary hospital in Tocantis, Brazil, were characterized phenotypically and genetically. A large part of S. marcescens isolates (n = 13, 24.07%) were classified as multidrug-resistant (MDR), with a high level of resistance to β-lactam antibiotics, aminoglycosides, quinolones, tigecycline and colistin. Our data confirmed the presence of genes in S. marcescens, which confer resistance to beta-lactam antibiotics, including carbapenems. PCR analyzes showed that all the isolates (n = 54, 100%) harbored the blaKPC-2 and blaTEM genes, 7 (12.96%) were positive for blaCTX-M-15.8 (14.81%) for the blaOXA-1 gene. The beta-lactamases genes blaVIM-1 and blaNDM-1, blaSHV and blaIMP-2 and the gene conferring resistance to colistin mcr-1 were not found. The ERIC-PCR technique was used to determine the clonal relationships between the strains. The results showed a high genetic similarity between the lines, indicating that S. marcescens circulating in this UTI are highly genetically related. The resistance pattern presented by S. marcescens clinical isolates and the potential transmission of these clones, observed in our study, is very worrying, since it is suggested that they are important disseminators of hospital infections. Therefore, measures that eliminate the sources of resistance development and the reservoirs of these bacteria are of extreme importance for the control of these infections.
Phenotypic and molecular characterization of antimicrobial susceptibility in Serratia marcencens isolated from patients in a tertiary hospital in the state of Tocantis
Keywords: Multidroga-resistentes; Genes; Serratia marcescens; Multidrug-resistant; CIENCIAS BIOLOGICAS::GENETICA